2020
DOI: 10.1097/iae.0000000000002805
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Three-Dimensional Fluorescein Angiography-Guided Pars Plana Vitrectomy for the Treatment of Proliferative Diabetic Retinopathy: The Maximized Utility of the Digital Assisted Vitrectomy

Abstract: Purpose: To show the usefulness of the intraoperative three-dimensional fluorescein angiography (3D-FA)-guided pars plana vitrectomy.Methods: The NGENUITY 3D visualization system was used for the digital assisted vitrectomy. Three-dimensional fluorescein angiography-guided pars plana vitrectomy was performed in three patients with vitreous hemorrhage secondary to proliferative diabetic retinopathy. We investigated both whether several angiographic findings can be successfully displayed on the screen during 3D-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 15 publications
(27 reference statements)
0
12
0
Order By: Relevance
“…In a previous report, 3D-FA-guided PPV made it possible to add the correct amount of retinal photocoagulation to NPA and identify the accurate size and orientation of active FVPMs in cases of proliferative diabetic retinopathy. 3 Similarly, in this study, the range of NPA secondary to BRVO was accurately identified, enabling additional performance of retinal photocoagulation with the sufficient and necessary number. It was also possible to perform maneuvers such as delamination and dissection of FVPMs while identifying the size and location of NVEs.…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations
“…In a previous report, 3D-FA-guided PPV made it possible to add the correct amount of retinal photocoagulation to NPA and identify the accurate size and orientation of active FVPMs in cases of proliferative diabetic retinopathy. 3 Similarly, in this study, the range of NPA secondary to BRVO was accurately identified, enabling additional performance of retinal photocoagulation with the sufficient and necessary number. It was also possible to perform maneuvers such as delamination and dissection of FVPMs while identifying the size and location of NVEs.…”
Section: Discussionmentioning
confidence: 63%
“…The previous and present studies clearly demonstrate that the 3D-FA is particularly useful for the treatment of ischemic retinal diseases, including BRVO with NVE. 3 Retinal vein occlusion sometimes develops into neovascularization on the disk and elsewhere, with traction retinal detachment, rhegmatogenous retinal detachment, epiretinal membrane, and VH, which requires PPV for the treatment. [4][5][6][7][8][9][10] Reports have shown that the outcomes of PPV are better when eyes underwent retinal photocoagulation in the NPA and had complete posterior vitreous detachment compared with only partial detachment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[1,2] Recent evidence supports particularly three-dimensionally (3D) visualized FA for clinical use. [3,4] However, intraoperative applicability of FA is limited given the complicated arrangement, invasiveness, associated risks, side effects, and the lack of objective/ automated vessel quantification, calling for alternative and more feasible techniques that lend themselves to be utilized day-to-day in the clinic.…”
Section: Introductionmentioning
confidence: 99%